2021
DOI: 10.1029/2020jc016511
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Signature of the Residual Foam in Breaking Waves

Abstract: Wave breaking plays a critical role in air-sea interaction processes in both the open ocean and the surf zone. The energy transferred from the atmosphere to the ocean through wind-wave generation is ultimately dissipated by wave breaking. Therefore, quantifying the energy dissipation due to wave breaking is directly relevant to wave prediction models used for operational sea-state forecasting and the impact of waves on coastal regions. At high-wind speeds, bubbles generated by large scale breaking waves are th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The brightness temperature of the residual foam was found by [27] to be as much as 0.3 K below the brightness temperature of the surrounding surface water. The cooling foam phenomenon was recently exploited by [28] to study energy dissipation due to breaking waves.…”
Section: Introductionmentioning
confidence: 99%
“…The brightness temperature of the residual foam was found by [27] to be as much as 0.3 K below the brightness temperature of the surrounding surface water. The cooling foam phenomenon was recently exploited by [28] to study energy dissipation due to breaking waves.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the potential non-uniform breaking velocity across an individual whitecap that results in zero average before the breaking front stops advancing. The second is that whitecap cooling is delayed due to the inequity in rates of foam cooling and renewal as identified by Masnadi et al (2020) [43]. This would have implication for breaking wave mechanics such as bubble penetration depth and degassing time.…”
Section: Discussionmentioning
confidence: 98%
“…The foam temperature showed no observable decrease until the foam remained on the surface for some time after the bubble generator had been turned off. Masnadi et al (2020) [43] found that cooling of surface foam is delayed until the rate of renewal of the foam by rising bubbles is less than the foam cooling rate. The same mechanism is likely responsible for the delayed cooling observed in the lab and supports the theory that whitecaps observed in IR remain in stage A briefly after breaking velocity reaches zero due to bubble plume dynamics.…”
Section: Linear Regression Modelmentioning
confidence: 99%
“…Experiments are performed in the Washington Air-Sea Interaction Facility (WASIRF) (Long, 1992;Masnadi et al, 2021), a long wave tank in which wind blows over the surface of the water (figure 7). The test section of the tank is 12.2 m long and 0.91 m wide, and is filled with tap water to a depth of 0.6 m, leaving 0.6 m of headspace for airflow.…”
Section: Methodsmentioning
confidence: 99%